Differential Properties of Venom Peptides and Proteins in Solitary vs. Social Hunting Wasps - Si Hyeock Lee; Ji Hyeong Baek; Kyungjae Andrew Yoon (Toxins, 2016)
The primary functions of venoms from solitary and social wasps are different. Whereas most solitary wasps sting their prey to paralyze and preserve it, without killing, as the provisions for their progeny, social wasps usually sting to defend their colonies from vertebrate predators. Such distinctive venom properties of solitary and social wasps suggest that the main venom components are likely to be different depending on the wasps’ sociality. The present paper reviews venom components and properties of the Aculeata hunting wasps, with a particular emphasis on the comparative aspects of venom compositions and properties between solitary and social wasps. Common components in both solitary and social wasp venoms include hyaluronidase, phospholipase A2, metalloendopeptidase, etc. Although it has been expected that more diverse bioactive components with the functions of prey inactivation and physiology manipulation are present in solitary wasps, available studies on venom compositions of solitary wasps are simply too scarce to generalize this notion. Nevertheless, some neurotoxic peptides (e.g., pompilidotoxin and dendrotoxin-like peptide) and proteins (e.g., insulin-like peptide binding protein) appear to be specific to solitary wasp venom. In contrast, several proteins, such as venom allergen 5 protein, venom acid phosphatase, and various phospholipases, appear to be relatively more specific to social wasp venom. Finally, putative functions of main venom components and their application are also discussed.